Supporting healthcare workers on front lines of the Covid-19 fight - Malerba, Mario; Ragnoli, Beatrice; Puca, Edmond; Pipero, Pellumb (Acta Biomedica Atenei Parmensis, 2020)
Un unexpected infection by a novel coronavirus (SAR CoV-2) started by the end of December in Wuhan, China, spreading all over other countries, and Italy was one of the most affected ones. WHO declared the pandemic on 11th March, 2020. Despite the numerous unknown aspects of this infection, the healthcare system had to face a multidimensional emergency. Albania, a small country with a geographical, historical and cultural relationship with Italy was one of the first countries giving support and starting a profitable collaboration focusing on the mission to provide the necessary help for the health care workers. In order to help the Italian healthcare system to face up to the situation two medical teams firstly (in March) and a group of 60 health care workers later in April were sent to Italy (Brescia Hospital) to support clinical activities in departments with COVID-19 patients. This important contribution showed the great solidarity and helped to strengthen the partnership between the two countries.